El-Niño temperature component, wind speed, red tide algae and seismodegasation - Lyushvin P.B.,; Buyanova M. O., (IJRDO-Journal of Applied Science, 2021)
Since the discovery of America, the Spaniards have known about the episodic appearance of the warm current of El-Niño near the Peruvian shores, which means "baby" in Spanish. Usually it manifests itself strongly after 6-7 years, extremely many times less often. The importance of his study is related to the hypothesis that he is the most important signal in the inter-annual climatic variability of the Earth. At the stage of identifying the genesis of El-Niño, oceanographers determine its appearance with a change in the direction of the prevailing winds, meteorologists consider the change of winds to be the result of water warming and compare the development of temperature anomalies with the difference in atmospheric pressure between Tahiti and Darwin (Australia). As a result, is it not clear whether changes in the wind field or water heating are primary, how are processes connected in the regions of Tahiti and Peru separated by thousands of miles? The result of the inexplicable confinement of the Peruvian El Niño to the Catholic nativity, the characteristic displacement of its main morose jet into the southern hemisphere, sometimes the isolation of the warming of various zones and its stagnation is the lack of a stable forecast of El Niño.This study focuses on the accompanying El-Niño haze of water, up to red tides. Such flowering of waters is characteristic of places of high concentration of biogens in situations of occasional weakening of mixing or arrival of significantly warmer waters (absolute temperature values are not so critical, temperature growth above the background is important, since the solubility of many gases will decrease). Weakening mixing leads to an increase in stratification, a decrease in the flow of nutrients. With the onset of phosphorus deficiency, some algae begin to mass-produce ichthyotoxins to protect against other phosphorus users and divide on a huge scale. As their number grows, the water becomes cloudy, acquires various colors, including brown-red (red tides). Thanks to the duckweed, the photic layer is reduced, the surface water is additionally warmed. Overheating stops when the flowering rate decreases, which is characteristic when the temperature decreases below the regionally critical one (the solubility of many gases increases), for example, with upwelling, storm stirring, intensification of currents whose waters are enriched with biogens or cool, and when seismodegasation is activated, which cool brings biogenes to the photographic layer.In the morose north of the Peruvian region rich in biogens, quasi-stiff conditions, haze and warmup of the waters are characteristic from November to February - confined to the Catholic nativity of the "boy." For the remaining tropical Latin American regions, the wind speed as a whole is many times higher, wind weakening is characteristic in spring. The crushing of the El-Niño language in the Latin American region, the isolated development of overheated waters and the stagnation of warming (except dynamic) are due to the entry of biogens to the surface during seismodegasation.The characteristic displacement of the El-Niño jet in the morose part of the Pacific Ocean into the southern hemisphere is associated with degassing north of the equator and Rossby waves at the equator. In the western and central Pacific Ocean, El-Niño certainly stagnates or disappears when earthquakes are activated near the Golden Country of Solomon, in the subduction zone (the only place in the tropics of contact, the subsidence of the Pacific Plate under the Indo-Australian), in the convergence zone of the Coralline and Fijian geoblocks, in the strait between lithospheric microplanes This strait is located at the border of the El-Niño emergence zone. What is this simple coincidence on a 30-year row or Pythagorean lever, the "string" at the equator on which "plays the bond" of earthquakes at the junction of geoblocks, what is the mechanism of this regional seismic effect on Earth?